2008
DOI: 10.1007/s11252-008-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential for golf courses to support restoration of biodiversity for BioBanking offsets

Abstract: In golf course development there is frequently remnant vegetation on the areas unused for infrastructure. We propose that these areas, together with a whole range of other reserves including sporting fields, cemeteries, railway reserves and educational facilities may be the source of degraded remnant vegetation and associated open space that could be used to provide offsets for biodiversity. We followed the changes in vertebrate biodiversity with low key alteration to management of the Camden Lakeside Golf Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Conversely, non-golfers expressed the exact opposite opinion, with 64% responding negatively due to perceived destruction of habitat [5]. Since that study's publication, however, extensive research has demonstrated the ecological benefits of golf courses, especially in urban settings [16,17,25,26,[28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, non-golfers expressed the exact opposite opinion, with 64% responding negatively due to perceived destruction of habitat [5]. Since that study's publication, however, extensive research has demonstrated the ecological benefits of golf courses, especially in urban settings [16,17,25,26,[28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Golf courses can play a vital role in enhancing biodiversity by providing a refuge for flora and fauna and improving connectivity between greenspaces [29]. Terman supports this point by identifying small naturalized ecosystems, such as those found on golf courses, as "habitat sinks" [24] (p. 192), meaning that these smaller habitats often support the mating activities of migrating populations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations